According to New Information Poet Rahmi Efendi From Harput And His Poem That Written in The Form of “Qasida” For The Rebuilding of Sare Hatun (Sarahatun) Mosque in Harput (Elazig) - Karataş, Ahmet (Fırat University, 2020)
One of the historical temples of Harput, the Sare Hatun (Sarahatun) mosque was demolished and rebuilt in the mid-nineteenth century as a serious repair was needed. All the people of Harput participated in this work from the rich to the poor, from the lord to the farmer. It was “İmamzade/ Müftüzade” Hacı Ahmed Efendi, one of Harput’s leading scholars and muftis, who encouraged them to such an favour. His student “Hoca” Rahmi Efendi is one of the most important poets of Harput in that century. For this mosque, whose construction was completed in 1259/1843, Rahmi Efendi wrote a thirty-one couplet history poem in the form of ode (“qasida”). The last four couplets of this poem are written on one of the outer walls of the mosque. This poem, which is not found in the old or new letters of the Divan of Rahmi Efendi, is included in the writing copy of the Efendigil Collection which was donated to the Library of the Faculty of Theology at Ankara University. This manuscript is written by Mehmed Kemaleddin Efendi, the Mufti of Mamuretülaziz, the son of Abdulhamid Hamdi and the grandson of Hacı Ahmed Efendi. Kemâleddin Efendi also included some anecdotes about Rahmi Efendi in a letter to his friend Ibnülemin Mahmud Kemal Inal. This information, which sheds light on Rahmi Efendi's relations with the state authorities of the time, his gentle, elegant, witty identity and poetic power, is discussed in this article for the first time.

Harput’un tarihî mabedlerinden Sâre Hatun (Sarahatun) Camii ciddi bir tamire ihtiyaç duyulduğu için XIX. asrın ortalarında temelden yıkılarak yeniden yapılmıştır. Bu faaliyete zengininden fakirine, ağasından çiftçisine bütün Harput-lular katılmışlardır. Onları böyle bir hayra teşvik eden ise Harput’un önde gelen âlim ve müftülerinden İmâmzâde/ Müftüzâde Hacı Ahmed Efendi olmuştur. Hacı Ahmed Efendi’nin talebesi Hoca Rahmî Efendi ise Harput’un o asırdaki önemli şâirlerinin başında gelmektedir. Rahmî Efendi 1259/1843’te inşaatı tamamlanan bu camiye kaside formunda otuz bir beyitlik bir tarih manzumesi yazmış, manzumenin son dört beyti caminin duvarlarından birine kitâbe olarak hakkedilmiştir. Rahmî Efendi’nin divânının ne eski ne de yeni harfli neşirlerinde bulunan bu kaside Ankara Üniversitesi İlâhiyat Fakültesi Kütüphanesi’ne bağışlanan Harputlu Efendigil Koleksiyonu’ndaki yazma nüshasında yer almaktadır. Bu yazma Hacı Ahmed Efendi’nin torunu Hacı Abdülhamid Hamdî Efendi’nin oğlu olan Ma?mûretü’l-azîz müftüsü Mehmed Kemâleddin Efendi tarafından istinsâh edilmiştir. Kemâleddin Efendi ayrıca dostu İbnülemin Mahmud Kemal İnal’ın ricâsı üzerine bir mektubun-da Rahmî Efendi’yle ilgili bazı anekdotlar da aktarmıştır. Rahmî Efendi’nin döne-min devlet erkânı ile münâsebetine, nâzik, zarif, nüktedân kimliği ve şâirlik kudre-tine ışık tutan bu bilgiler söz konusu kasideyle birlikte ilk defa bu makalede ele alınmıştır. Bu makalede ayrıca Rahmî Efendi’nin vefât tarihine ve divânının terti-bine dair yeni tespitlere de yer verilmiştir.
YENİ BİLGİLER IŞIĞINDA HARPUTLU ŞÂİR RAHMÎ EFENDİ VE SÂRE HATUN (SARAHATUN) CAMİİ’NİN YENİDEN İNŞÂSINA YAZDIĞI KASİDE